Urologic Complications following Gynecologic Surgery in a Sub-Saharan West African Country - Dehi Boston Mian; Virginie Angoi; Raoul Kasse; Alexis Yao; Sophia Akinloye; Fatoumata Ampoh; Koffi N'Guessan; Serge Boni (IMR Press, 2023)
Background: Urological trauma is a dreaded complication of gynecological or obstetrical surgery and its incidence is poorly documented in resource limited settings can cause a major health problem. The objective of this study is to determine the clinical, therapeutic and evolutionary aspects of iatrogenic urological lesions in a low- and middle-income country (LMIC). Methods: A retrospective, descriptive study conducted for 5 years at the obstetrics and gynecology department of the university hospital of Cocody. It concerned all gynecological surgery performed in the department. All Urinary Tract Injuries (UTI) during surgery were recorded. UTI occurring outside this scenario were excluded. The socio-demographic features, clinical data, intraoperative UTI features, and treatment outcome parameters were studied. Statistical analysis was carried out using Epi Info 3.5.1 2008 software. Results: We recorded 46 cases of UTI (4.0%) including bladder (n = 33 or 71.7%), ureter (n = 8 or 17.4%) and both bladder and ureteral lesions (n = 5 or 10.9%). The average age of patients was 29 years. The UTI were suspected during the initial surgery by hematuria (52.2%), or intraoperative visualization (23.07%). Postoperative diagnosis of UTI was made in patients presenting with signs of peritonitis (3.84%). The UTI were immediately repaired (96.16%) by simple suturing of bladder or cystorraphy (84.64%), ureter: or ureterorraphy (4.3%), ureterostomy (4.3%) and removal of ureteral strictures (4.3%). Postoperative complications (15.36%) included urogenital fistulae (50%), urinary tract infection (25%) and acute peritonitis (25%). The average length of stay in the urology department was 45 ± 5 days. No maternal deaths were reported. Conclusions: Urologic complications associated with gynecologic procedures are sometimes unavoidable but can be reduced by complying with standard surgical guidelines. Bladder trauma were the most common iatrogenic lesions, however ureteral injuries are feared because of their more complex treatment. Treatment strategies should be dependent on location and length of injury, and surgical possibilities.